2007
DOI: 10.1073/pnas.0701912104
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of the NC80 motif is critical for the photoactivation of Arabidopsis CRY2

Abstract: Cryptochromes are blue light receptors that regulate photomorphogenesis in plants and the circadian clock in animals and plants. Arabidopsis cryptochrome 2 (CRY2) mediates blue light inhibition of hypocotyl elongation and photoperiodic control of floral initiation. CRY2 undergoes blue light-induced phosphorylation, which was hypothesized to be associated with CRY2 photoactivation. To further investigate how light activates CRY2, we analyzed the physiological activities and phosphorylation of various CRY2 fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
150
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(167 citation statements)
references
References 41 publications
9
150
0
8
Order By: Relevance
“…(iv) All bona fide CRYs have C-terminal extensions beyond the photolyase homology region (PHR), which range from ∼20 amino acids in Drosophila CRY to ∼250 amino acids in Arabidopsis CRY1 (2,14,36). (v) Light causes a significant conformational change in the C-terminal extensions of Arabidopsis CRY1 (14,43) and Drosophila CRY (this work) as revealed by the effect of light on the partial proteolysis profile. (vi) The C-terminal extensions of Arabidopsis CRYs when separated from the PHR domain confer a constitutive "light-on" phenotype (15).…”
Section: Discussionmentioning
confidence: 99%
“…(iv) All bona fide CRYs have C-terminal extensions beyond the photolyase homology region (PHR), which range from ∼20 amino acids in Drosophila CRY to ∼250 amino acids in Arabidopsis CRY1 (2,14,36). (v) Light causes a significant conformational change in the C-terminal extensions of Arabidopsis CRY1 (14,43) and Drosophila CRY (this work) as revealed by the effect of light on the partial proteolysis profile. (vi) The C-terminal extensions of Arabidopsis CRYs when separated from the PHR domain confer a constitutive "light-on" phenotype (15).…”
Section: Discussionmentioning
confidence: 99%
“…All nonvisual photoreceptors that have been analyzed to date including phytochrome, phototropin, and BLUF proteins are homodimers (Christie 2007). It has been reported that AtCRY1 and AtCRY2 form homodimers and heterodimers that are essential for their in vivo function (Sang et al 2005;Yu et al 2007). In contrast, it was recently reported that Drosophila CRY is a monomer (Berndt et al 2007), whereas coimmunoprecipitation experiments with recombinant mammalian CRYs suggest that they form homoand heterodimers (Partch 2006).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Biochemical and biophysical tests show that the carboxy-terminal domains of CRYs are highly unstructured when expressed alone Kottke et al 2006) but assume a rigid structure by interacting with the PHR domain . Light-induced conformational change from order to disorder in AtCRY1 has been proposed to initiate the photosignaling reaction Kottke et al 2006;Yu et al 2007).…”
Section: Structures Of Photolyase and Cryptochromementioning
confidence: 99%
“…The long C-terminal extension (CCT) of plant cryptochromes is sufficient for constitutive activation of the signaling cascade (12). This effect could be narrowed down in sequence to an 80-residue motif that includes a few residues of the PHR and the adjacent region of the CCT (13). Binding of the PHR to the CCT in the dark is considered to act as a repressor of this motif.…”
mentioning
confidence: 99%